Dextrose‐containing intraoperative fluid in neonates: a randomized controlled trial. Issue 6 (16th April 2016) - Datta, Priyankar K.; Pawar, Dilip K.; Baidya, Dalim K.; Maitra, Souvik; Aravindan, Ajisha; Srinivas, Maddur; Lakshmy, Ramakrishnan; Gupta, Nandita; Bajpai, Minu; Bhatnagar, Veereshwar; Agarwala, Sandeep
Summary: Background: Glucose requirement in neonates during surgery and the impact of glucose supplementation on neonatal metabolism remain unclear. Aim: This study was designed to identify an appropriate perioperative fluid regimen in neonates which maintains carbohydrate and lipid homeostasis. Methods: Forty‐five neonates undergoing primary repair of a trachea‐esophageal fistula were randomly allocated into three groups. During surgery, the neonates received either 1% dextrose in Ringer lactate (RL) (group D1) at 10 ml·kg −1 ·h −1, or 2% dextrose in RL (group D2) at 10 ml·kg −1 ·h −1, or 10% dextrose in N/5 saline at 4 ml·kg −1 ·h −1 and replacement fluid with 6 ml·kg −1 ·h −1 of RL (group D4). Glucose homeostasis, electrolyte balance, acid–base status, and endocrine and metabolic parameters were compared among the groups during the perioperative period. Results: Blood glucose increased in all the three groups at the end of surgery, with no significant difference in blood glucose and incidence of hyperglycemia (BG > 150 mg·dl −1 ) among them. At 24 h after surgery, blood glucose and incidence of hyperglycemia was significantly higher in Group D1 compared to Group D4. Base excess, bicarbonate, lactate, and pH showed a significant fall in Group D1. There was no significant difference in serum‐free fatty acids, serum beta‐hydroxy butyrate, and serum cortisol in three groups. At the end of surgery, serum insulin was significantly lower and glucagon : insulin (G : I) ratio was higher in Group D1 compared to Group D4. Conclusions: All three solutions, when infused at 10 ml·kg −1 ·h −1, are equally effective in maintaining glucose homeostasis, but 1% dextrose‐containing fluid promotes catabolism, insulin resistance, rebound hyperglycemia, and acidosis. Therefore, 2–4% dextrose‐containing fluids is more suitable compared to 1% dextrose‐containing fluids for use during major neonatal surgeries requiring average fluid infusion rate of 10 ml·kg −1 ·h −1 . Abstract :